Activación de los músculos del tronco en ejercicios de estabilización raquídea - Vera-Garcia, F. J.; Barbado, D.; Flores-Parodi, B.; Alonso-Roque, J. I.; Elvira, J. L. L. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2013)
The aim of this study was to analyze the trunk muscle coactivation during spine stabilization exercises. The electromyography of rectus, obliquus externus and obliquus internus abdominis and erector spinae was recorded while performing the back bridge, the front bridge and the right and left side bridge exercises. The muscular activation levels needed to stabilize the trunk in the bridge exercises were low or moderate. Abdominal muscles were mainly activated in the frontal and lateral bridge, and erector spinae in the back bridge. All trunk muscles from the side of the arm of support were activated during the lateral bridges. On the contrary, frontal and back bridges isolated the abdominal and lumbar muscle activation, respectively. These results may facilitate the stabilization exercise selection to design trunk muscle conditioning programs.